By Hook Or By Crook: From Pedicab Drivers to Company Owners through Start-Up Worker Co-Operatives - Novita Puspasari; Yanuar E Restianto (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2020)
Disruption of information technology has threatened several jobsin the informal sector. As a result, the income gap between the rich and the poor can get wider. In Purwokerto, Central Java, the emergence of online application-based transportation has disrupted the work of becak drivers. This research used actionresearch method. In action research, researcher conduct research and at the same time make changes and interventions to the object. In the first stage, diagnosis,it was found that becak drivers' work was no longer competitive. Therefore, the intervention made with establishing a start-up worker co-operativesmodel, an online-based worker-cooperative for former becak drivers. In this model, becak drivers are directed to work in service sectors, such as cleaning service, gardener, plumber, and other service works.Orderingprocess can bemade through online application which can be downloaded for free in android devices.There are two implications in this study. First, in theory, this study offers a relatively new model, start-up worker co-operative. This model enables all workers to be owners in their co-operative company. Second, in practice, if successfully implemented, this model can be replicated for other sectors and other regions. As a result, start-up worker co-operative can be one solution to overcome income inequality.